Business Risk Management Planning for Junior Auditor Positions in Public Accounting Firms - Antoni Ang, Meiga Putri; Yuwono, Wisnu (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
The role and position of public accountants such as auditors are criticized for doubting their professionalism and independence. This condition results in the potential become high risks in KAP, the risks also affect the author who serves as a Junior Auditor at Public Accounting Firm. In this case, the author plans business risk management in the work of the Junior Auditor position to minimize the risk of material errors in doing his work. The research method uses the results of interviews and brainstorming, the results of which are used as events that become the object of research on potential risks that are likely to arise if these risks occur. The results of the event will form a risk register which will be an input in making Qualitative Risk Identification. The results of the study are 5 types of risk events and triggers that occur in Public Accountant, namely; complex transactions (high risk), uncooperative clients (medium risk), high audit schedule (medium risk), final approval audit report (medium risk), and business audit risk (medium risk).